AAN Guideline on Steroids and Antivirals for Bell Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
The Guideline Development Subcommittee of the AAN provides an update of the 2001 evidence-based practice guideline for the treatment of Bell palsy.